Determination of Chronic Ecotoxicity to Danio rerio - Bertoletti, Eduardo (Ecotoxicology and Environmental Contamination, 2009)
Although the fishes Danio rerio and Pimephales promelas belong to the family Cyprinidae, the original methods described for ecotoxicological assay using these species have experimental differences, which cause some problems when results are compared. In order to verify the equivalence of toxic effects for these fish species, assays with Danio rerio were performed using 10 chemicals under the same experimental conditions described for Pimephales promelas assay. In such conditions it was demonstrated that the calculated CVest (estimated chronic value) to Danio rerio, or 168h-LC15 multiplied by 0.3 factor, generates equivalent values to ≥ 28 days chronic assays with Pimephales promelas. The results of this paper were the basis for the ABNT (Associação Brasileira de Normas Técnicas) assay standardization to evaluate toxic chronic effects to fish.